Parenting Patterns in the Perspective of Hadith: A Literature Review - Nurul Faizatus Sholikah; Saiful Amien; Moh. Nurhakim (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2025)
This article aims to describe the concept and urgency of child-rearing according to the Prophet Muhammad saw based on authentic hadiths, as well as to explain its contribution to shaping children's character from an Islamic educational perspective. This study employs a qualitative approach using library research methods. Primary sources include authoritative hadith collections such as Sahih al-Bukhari, Sahih Muslim, Sunan Abu Dawud, Sunan at-Tirmidzi, and Musnad Ahmad. Secondary sources include hadith commentaries and contemporary Islamic educational literature. Data collection techniques were conducted through documentary studies, then analysed using content and thematic analysis approaches. Data validity was maintained through source triangulation and hadith quality checks using the takhrij method. The research findings indicate that the concept of the Prophet Muhammad's parenting style includes compassion, exemplary behaviour (uswah hasanah), respect for the child's existence, instilling manners, and early spiritual education. This pattern is not only normative but also practical and contextual for application in child-rearing in the modern era, which is filled with moral and social challenges. These findings contribute theoretically to the development of Islamic education science and practically to Muslim families in establishing sunnah-based parenting patterns.